Agricultural research and urban poverty in India - Fan, Shenggen (International Food Policy Research Institute, 2002)
Using a similar analytical approach to a study in China, this paper analyzes the impact of agricultural research on urban poverty reduction in India. State level data from 1970 to 1995 were used in the empirical analysis. It is found that in addition to its large impact on rural poverty reduction, agricultural research investments have also played a major role in the reduction of urban poverty. Agricultural research investments increase agricultural production, and increased production in turn lowers food prices. The urban poor often benefit proportionately more than the non-poor since they spend 50-80% of their income on food. Among all the rural investments considered in this study, agricultural research has the largest impact on urban poverty reduction per additional unit of investment. The results from this study are similar to earlier findings for China. Today, urban poverty still accounts for one quarter of total poverty in India, and this share is expected to rise in the future. Policymakers cannot afford to be complacent about this trend and continued investments are still needed to keep food prices low. Among all government policy instruments, increased agricultural research is still the most effective way to achieve this objective.